WoCoVA consensus on the clinical use of in-line filtration during intravenous infusions: Current evidence and recommendations for future research. Issue 2 (March 2022) - Van Boxtel, Ton; Pittiruti, Mauro; Arkema, Annemarie; Ball, Patrick; Barone, Giovanni; Bertoglio, Sergio; Biffi, Roberto; Dupont, Christian; Fonzo-Christe, Caroline; Foster, Jann; Jones, Matthew; Keck, Cornelia; et al.
The need for filtering intravenous infusions has long been recognized in the field of venous access, though hard scientific evidence about the actual indications for in-line filters has been scarce. In the last few years, several papers and a few clinical studies have raised again this issue, suggesting that the time has come for a proper definition of the type of filtration, of its potential benefit, and of its proper indications in clinical practice. The WoCoVA Foundation, whose goal is to increase the global awareness on the risk of intravenous access and on patients' safety, developed the project of a consensus on intravenous filtration. A panel of experts in different aspects of intravenous infusion was chosen to express the current state of knowledge about filtration and to indicate the direction of future research in this field. The present document reports the final conclusions of the panel.